Orders of worth and the moral conceptions of health in global politics - Tine Hanrieder (International theory: a journal of international politics, law and philosophy, 2016)
– The article analyzes the contested concept of global health through the lens of orders of worth. Drawing on pragmatist political and social theory, especially the work of Boltanski and Thévenot, I conceptualize orders of worth as moral narratives that connect visions of universal humankind to ideas about moral worth and deficiency. They thereby differ from the self/other narrative of political identity that is emphasized in International Relations scholarship. Orders of worth do not pitch a particularistic identity against foreign identities, but tie collective identity to a higher common good. They provide tools for moral evaluation and the justification of hierarchy. I use this heuristic to reconstruct four main conceptions of health in global politics: The order of survival, the order of fairness, the order of production, and the order of spirit. Each of them articulates a distinct political identity, as 'we species', 'we liberals', 'we bodies' and 'we souls', and implies different notions of virtuous and selfish conduct in the global community. These orders are derived from scholarly writings and the policies of global health institutions. Finally, I discuss the nature of compromises between the four orders regarding contested issues such as health emergencies or digital medicine.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; pragmatism; global health; orders of worth; health ethics; identity; valuation sociology